2015
DOI: 10.1016/j.cbi.2014.10.032
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of ER stress prevents post-infarction-induced cardiac rupture and remodeling by modulating both cardiac apoptosis and fibrosis

Abstract: Endoplasmic reticulum (ER) stress is implicated in the pathophysiology of various cardiovascular diseases, but the role of ER stress in cardiac rupture and/or remodeling after myocardial infarction (MI) is still unclear. Here we investigated whether ER stress plays a major role for these processes in mice. We ligated the left coronary artery (LCA) without reperfusion in mice and administered either NaCl or 4-phenylbutyric acid (4-PBA, 20 mg/kg/d) intraperitoneally for 4 weeks. Cardiac rupture rates during the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
52
1
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(61 citation statements)
references
References 45 publications
5
52
1
3
Order By: Relevance
“…4-PBA was able to reduce ER stress factors, mitigate ISO-induced cardiac damage, and prevent interstitial collagen deposition (Ayala et al, 2012). In another in vivo model of cardiac remodeling and fibrosis, it was demonstrated that 4-PBA treatment increased overall survival through the reduction of myocardial infarct induced damage and subsequent cardiac rupture (Luo et al, 2015). This study also provided evidence that 4-PBA can down regulate ER stress factors and decrease the synthesis of pro-fibrotic proteins (Luo et al, 2015).…”
Section: The Effects Of 4-pba On Neurological Diseases and Models Of mentioning
confidence: 87%
“…4-PBA was able to reduce ER stress factors, mitigate ISO-induced cardiac damage, and prevent interstitial collagen deposition (Ayala et al, 2012). In another in vivo model of cardiac remodeling and fibrosis, it was demonstrated that 4-PBA treatment increased overall survival through the reduction of myocardial infarct induced damage and subsequent cardiac rupture (Luo et al, 2015). This study also provided evidence that 4-PBA can down regulate ER stress factors and decrease the synthesis of pro-fibrotic proteins (Luo et al, 2015).…”
Section: The Effects Of 4-pba On Neurological Diseases and Models Of mentioning
confidence: 87%
“…In this study, we shed light on the temporal relationship between ER stress and LVH, demonstrating that the ER stress response persists up to 4 weeks after TAC. Although mechanisms by which ER stress modulates myocardial hypertrophy and interstitial fibrosis remain unclear, some suggest involvement of CaN-MEF2c signaling pathways in cardiomyocytes [7] and TGFβ1-Smad2/3 in cardiac fibroblasts [10]. Further investigations are needed to detail the putative mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…The animals were housed in the 12-12 cycle environment, and checked three times each day. The dosage of 4-PBA was determined according to our previous study [10]. At the end of 4 weeks, the surviving animals were subjected to echocardiographic imaging, then euthanized for autopsy, and histological analysis, and western blotting.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…I/R injury rats are accompanied by myocardial infarction (MI), and increased myocardial infarct size and myocardial enzyme activity were observed [106] . Luo et al [110] reported that MI induced ERS and provoked cardiac apoptosis and fibrosis by increasing the expression of ERS markers GRP78 and CHOP, pro-apoptotic proteins Bax and caspase 3, and pro-fibrotic proteins transforming growth factor-beta 1 (TGF-β1) and Smad 2/3, culminating in cardiac rupture and remodeling. Li et al [111] reported that ERS contributed to MI through the activation of NADPH oxidase.…”
Section: Endoplasmic Reticulum Stress Regulates Cardiovascular Physiomentioning
confidence: 99%